2016
DOI: 10.1111/iej.12626
|View full text |Cite
|
Sign up to set email alerts
|

A quality assessment of randomized controlled trial reports in endodontics

Abstract: The quality of RCT reports in key areas for internal validity of the study was poor. Several measures, such as compliance with the CONSORT guidelines, are important in order to raise the quality of RCTs in Endodontics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 51 publications
1
30
2
1
Order By: Relevance
“…A recent study confirms the low quality of randomized controlled trials in endodontics (Lucena et al . ). Although a few BECs have shown promising results in clinical applications, the number of investigations that evaluated them was low, and their long‐term efficacy is unknown.…”
Section: Resultsmentioning
confidence: 97%
“…A recent study confirms the low quality of randomized controlled trials in endodontics (Lucena et al . ). Although a few BECs have shown promising results in clinical applications, the number of investigations that evaluated them was low, and their long‐term efficacy is unknown.…”
Section: Resultsmentioning
confidence: 97%
“…); nevertheless, reports of many trials remain suboptimal (Chan & Altman ), including in the field of Endodontics (Lucena et al . , Nagendrababu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, papers published in the last 10 years have only a small probability of appearing in the list of the most frequently cited articles in any field of research. Even so, 73 out of the 100 Top 100 evidence level 1 articles in endodontics Ahmad et al papers were published in the last 10 years, that is field of Endodontics (Lucena et al 2017, Nagendrababu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of homogeneous RCTs can be pooled statistically by conducting meta-analyses that lay at the pinnacle of the hierarchy of evidence (Ismail & Bader 2004, Dhar 2016. This distilled and synthesized evidence then forms the foundation to create evidence-based guidelines and policies by providing accessible data to support informed decision-making (Dhar 2016, Lucena et al 2017. However, RCTs are often subject to bias if they have weak study designs, retrospective power calculations and/or poorly reported methodological standards, such as unclear description of the sampling or randomization procedures, blinded interventions or evaluation of outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…The CONSORT statements are the most widely used, frequently endorsed and well-reported in the literature. It has been reported that the CONSORT statements have improved the quality of RCTs in the medical and dental fields (Kane et al 2007, Vere & Joshi 2011, Lucena et al 2017). Furthermore, a number of complementary guidelines have been developed by modifying the CON-SORT statements to specific medical specialties, such as infertility treatments (Improving the Reporting of Clinical Trials of Infertility Treatments (IMPRINT)) (Harbin Consensus Conference Workshop Group 2014), herbal interventions (Gagnier et al 2016) and acupuncture (STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA)) (MacPherson et al 2010).…”
Section: Introductionmentioning
confidence: 99%